(untitled) (Medico Legal Update, 2020)
Background: Type 2 Diabetes mellitus is a group of metabolic disease characterized by increase blood glucose level (hyperglycemia) resulting from either defect in insulin production by pancreas or increase insulin resistance that lead to decrease insulin effect in the body. prediabetes It is stage before diabetes mellitus including impaired fasting glucose (IFG)where the fasting glucose level (6.1-7.O mmol/L) and impaired glucose tolerance (IGT after glucose load) glucose level (7.8-11 mmol/L).(salusin-?) It is a newly glass of peptide it is synthesized in many body tissues, like (skeletal muscle, human vascular smooth muscle cells, and endothelial muscle) it have important role in Diabetes pathogenesis it has been reported to involve in vascular inflammation and the relation between salusin ? and diabetes through endothelial injury, salusin ? increase inflammation in diabetes. It have essential role in pathological endothelial dysfunction. Method: by using ELISA kit, we measured serum level of salusin ? in 30 patients with prediabetes and 30 patients with type 2 DM compare with 30 healthy volunteers enlisted as normal controls. Result: serum salusin ? level in patient with type 2 DM were significantly higher than prediabetes group and normal subjects. Salusin ? in prediabetes group no significant higher than in healthy control subjects. Conclusion: Serum Salusin ? level in patients with type 2 DM are expressed at significantly high levels were no difference in Salusin ? level of prediabetes group and normal control subjects.